The First Metronidazole-Resistant Bacteroides Species Isolated at Marmara University Hospital: Bacteroides thetaiotaomicron - (:unkn) unknown (ANKARA MICROBIOLOGY SOC, 2013)
Bacteroides species, the predominant constituents of the human intestinal microbiota can cause serious intraabdominal and postoperative wound infections and bacteremia. Moreover, these bacteria are more resistant to antimicrobial agents than the other anaerobes. The limited number of the antimicrobials, such as carbapenems, beta-lactam/beta-lactamase inhibitors and nitroimidazoles are highly effective in eliminating Bacteroides. However, a few metronidazole-resistant isolates have been reported from several countries recently. The nim genes (nim A-G) are suggested to be responsible for the majority of the metronidazole resistance. Here, we describe a metronidazole-resistant Bacteroides thetaiotaomicron isolated from a blood culture. A gram-negative obligate anaerobic rod was isolated from the postoperative 5th day blood culture of a 62-year-old male patient with adenocarcinoma of the pancreas head. The strain was identified as B.thetaiotaomicron by using a combination of conventional tests and commercially available biochemical kits. Antimicrobial susceptibility testing was performed by agar dilution method. The resistance genes were investigated by means of PCR using specific primer pairs for nim gene. The purified PCR product was sequenced and analyzed by comparison of the consensus sequences with GenBank sequences. The MIC for metronidazole was 16 mg/L. Although the strain was intermediate according the CLSI criteria, it was resistant (>4 mg/L) according to EUCAST criteria. The isolate was nim gene positive, and nucleotide sequencing of the PCR product shared 100% similarity with nimE gene (emb vertical bar AM042593.1 vertical bar). On the other hand the isolate was susceptible to carbapenems and sulbactam-ampicillin. Following administration of ampicillin-sulbactam, the patient's fever disappeared after 24 hours. The clinical condition improved considerably and he was discharged at day 8. The patient was followed up at the medical oncology clinic; however he died due to disease progression six months after surgery. Since anaerobic bacteremia is associated with high mortality rate, prompt diagnosis and proper management are critical. The studies on Bacteroides bacteremia have revealed adverse outcomes in patients receiving antibiotics to which the bacterium was resistant. In the present case, the metronidazole-resistant organism would be reported as susceptible according to CLSI breakpoint value and on account of this result the treatment might lead to clinical failure. Therefore EUCAST MIC values seem to be more rational in case of Bacteroides antibiotic susceptibility testing.
Keywords: Bacteroides thetaiotaomicron; metronidazole; resistance; nim gene; Turkey; ANTIBIOTIC-RESISTANCE; FRAGILIS GROUP; STRAINS; GENES; PCR